Bite-on-bite biopsies for the detection of residual esophageal cancer after neoadjuvant chemoradiotherapy - van der Bogt, Ruben D.; van der Wilk, Berend J.; Oudijk, Lindsey; Schoon, Erik J.; van Lijnschoten, Gesina; Corporaal, Sietske; Nieken, Judith; Siersema, Peter D.; Bisseling, Tanya M.; van der Post, Rachel S.; Quispel, Rutger; van Tilburg, Arjan; Oostenbrug, Liekele E.; Riedl, Robert G.; Hol, Lieke; Kliffen, Mike; Nikkessen, Suzan; Eyck, Ben M.; van Lanschot, J. Jan B.; Doukas, Michael; Spaander, Manon C. W. (Endoscopy, 2022)
Background Active surveillance after neoadjuvant treatment is increasingly implemented. The success of this strategy relies on the accurate detection of residual cancer. This study aimed to assess the diagnostic value of a second (bite-on-bite) biopsy for the detection of residual esophageal cancer and to correlate outcomes to the distribution of residual cancer found in the resection specimen. Methods A multicenter prospective study of esophageal cancer patients undergoing active surveillance after neoadjuvant chemoradiotherapy was performed. At clinical response evaluations, an upper gastrointestinal (GI) endoscopy was performed with at least four bite-on-bite biopsies of the primary tumor site. First and second biopsies were analyzed separately. Patients with histopathological evidence of residual cancer were included in the primary analysis. Two pathologists blinded for biopsy outcome examined all resection specimens.Results Between October 2017 and July 2020, 626 upper GI endoscopies were performed in 367 patients. Of 138 patients with residual cancer, 112 patients (81 %) had at least one positive biopsy. In 14 patients (10 %) only the first biopsy was positive and in 25 patients (18 %) only the second biopsy (P = 0.11). Remarkably, the rates of patients with tumor-free mucosa and deeper located tumors were higher in patients detected by the first biopsy. The second biopsy increased the false-positive rate by 3 percentage points. No adverse events occurred. Conclusions A second (bite-on-bite) biopsy improves the detection of residual esophageal cancer by almost 20 percentage points, at the expense of increasing the false-positive rate by 3 percentage points. The higher detection rate is explained by the higher number of biopsies obtained rather than by the penetration depth.